Case Analysis of the Annulled Women and their Manner in Moving Forward - Ricafrente, Jellian (International Journal of Arts, Sciences and Education, 2022)
This particular study was conducted to investigate the causes as a ground for the nullity of marriage, to define the problems encountered during the case process and to know how people who seek annulment feel into making-up stories or lying about their previous failed marriage. In order to gather the necessary data, observation and interviews were conducted to the annulled women who have undergone the process of Declaration of Nullity of Marriage. Through careful treatment of data, the study ended up concluding that psychological incapacity is the only cause in the declaration of the nullity of the participants’ marriage. Descriptions of the psychological incapacity based on this research were given and summarized as the husband is a drug addict and liar; the wife was always beaten by the dependent, alcoholic, gambler, and drug dependent husband. Husband who should be the financial provider has no permanent work and the worst and most painful for a mother was when the children were beaten by their father who can be psychologically classified as anti-social with the underlying narcissistic personality traits, pathological lying, and pathological gambler with impulse-control disorder. The problems encountered by battered women when filing for a nullity of marriage is its long process and the large amount of money to be paid for a package deal process to the lawyer. Annulled women described themselves after their nullity of marriage as being free from pains, they become stronger and persevering. They gained more self-confidence because they are free from emotional burdens, they are working hard for their children and most of all; they now have a “friendly” life. In moving forward, they practiced meditation, and exercise thinking aloud on how their case on nullity of marriage would be successful. Social support also played a very important part in letting go as well as no feeling of bitterness which helps them in looking for a positive outlook in life after their annulment. As an upshot of this study and to be able to help the abused women to expedite the process of annulment, a resolution addressing the problem encountered was crafted. Moreover, based on findings, a realization was drawn like: “psychological incapacity” to the most serious cases of personality disorders clearly demonstrative of an utter insensitivity or inability to give meaning and significance to the marriage.